Extreme heat and its impact on the workplace - Selma Penalva, Alejandra (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
Although it has not been an event that received the media attention it deserved, in the last three years something very important has happened within Labor Law: the legislator has finally become aware of the significant exposure of workers to environmental risks, especially those who do not perform their duties in a workplace, and has approved what is undoubtedly a milestone in the history of Labor Law: the minimum environmental conditions that must be guaranteed in any work performed outdoors (cf. the new Sole Transitional Provision of Royal Decree-Law 4/2023, introduced into Royal Decree 486/1997, which establishes the minimum safety and health provisions in workplaces). However, despite its commendable intention, the legislator has been somewhat weak in its provisions, resulting in an ambiguous regulation.This paper focuses on evaluating the various unclear aspects of the new regulation and on assessing the real scope that its provisions may have in practice, highlighting that its very broad margin of indeterminacy undoubtedly reduces the practical effectiveness of this new regulation and delegates fundamental aspects of occupational risk prevention to collective bargaining that should have been addressed more decisively in the text of the regulation itself.
Keywords: Disaster; climate emergency; occupational risk prevention; extreme heat; torrential rains; outdoor work